Juror #3 - Patterson, James, 1947-; Allen, Nancy (Lawyer) (New York : Little, Brown and Company, 2018)
Struggling young attorney Ruby Bozarth defends a man she passionately believes to be innocent in a first murder trial that could make or break her career, only to discover that the case is affected by a juror's shocking secret.
Keywords: Women lawyers -- Fiction; Trials (Murder) -- Fiction; Rosedale (Miss.) -- Fiction; Detective and mystery fiction; Legal fiction (Literature); Thrillers (Fiction); Mystery fiction; Legal stories